2004
DOI: 10.3201/eid1005.030735
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Commensal Flora of Pig Farmers

Abstract: We assessed the quantitative contribution of pig farming to antimicrobial resistance in the commensal flora of pig farmers by comparing 113 healthy pig farmers from the major French porcine production areas to 113 nonfarmers, each matched for sex, age, and county of residence. All reported that they had not taken antiimicrobial agents within the previous month. Throat, nasal, and fecal swabs were screened for resistant microorganisms on agar containing selected antimicrobial agents. Nasopharyngeal carriage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 27 publications
(24 reference statements)
7
95
1
2
Order By: Relevance
“…Another factor that might be contributing to the emerging resistance problem is the use of antibiotics or analogous compounds in agriculture. The use of these compounds in agricultural settings may lead to a more constant selective pressure for resistance to develop and could potentially contribute to a larger global resistance reservoir with potential introduction, for example via opportunistic pathogens, into the clinical environment (Aubry-Damon et al, 2004;Heuer & Smalla, 2007).…”
Section: Impact Of Antimicrobial Agents On the Spread And Stabilizatimentioning
confidence: 99%
“…Another factor that might be contributing to the emerging resistance problem is the use of antibiotics or analogous compounds in agriculture. The use of these compounds in agricultural settings may lead to a more constant selective pressure for resistance to develop and could potentially contribute to a larger global resistance reservoir with potential introduction, for example via opportunistic pathogens, into the clinical environment (Aubry-Damon et al, 2004;Heuer & Smalla, 2007).…”
Section: Impact Of Antimicrobial Agents On the Spread And Stabilizatimentioning
confidence: 99%
“…As pig farming was the only common denominator in these cases it was deduced that there may be a link between pig farming and increased risk of MRSA infection; indeed colonisation by MRSA in pig farmers was found to be almost twice that of the general population (Aubry-Damon et al, 2004). Pigs have been similarly implicated as a reservoir of MRSA in France, a study of pig isolates found all to be non-typeable by pulsed-field gel electrophoresis (PFGE), the so-called "gold standard" for MRSA typing (Armand-Lefevre et al, 2005), and the association between PFGE non-typeable strains and pig farming has gained further empirical support (Huijsdens et al, 2006).…”
Section: B Environmental Reservoirs Of Mrsamentioning
confidence: 99%
“…Tetracyclines are among the most used in pig farming and previous studies demonstrated their persistence in manure and soil [1][2][3] and possible exposition of farmers during application of organic fertilizers to soil [4].…”
Section: Introductionmentioning
confidence: 99%